An Intersectional Analysis of Technology-Facilitated Abuse: Prevalence, Experiences and Impacts of Victimization - Flynn, Asher (The British journal of criminology, 2024)
Technology-facilitated abuse (TFA) is a growing problem. This article explores lifetime victimization experiences of TFA, presenting findings from the first study to establish a reliable national prevalence estimate for victimization in Australia, using a general adult population sample (n = 4,562) and 20 qualitative interviews with adults who have experienced TFA. Key findings include an overall high lifetime victimization prevalence (one in two Australians), high negative emotional impacts and severe mental distress among some marginalized groups. Our findings lend support for the utility of marginalization and intersectional theories in understanding the prevalence and negative impacts of TFA and address gaps in knowledge of how TFA victimization may differentially impact marginalized groups within an adult population. We argue that TFA research, policy and practice must be more attentive to intersecting and marginalized identities including and beyond gender.